Identification of natural rubber degradation gene in Rhizobacter gummiphilus NS21. Issue 3 (4th March 2017) - Kasai, Daisuke; Imai, Shunsuke; Asano, Shota; Tabata, Michiro; Iijima, So; Kamimura, Naofumi; Masai, Eiji; Fukuda, Masao
Abstract: A Gram-negative rubber-degrading bacterium, Rhizobacter gummiphilus NS21 grew and produced aldehyde metabolites on a deproteinized natural rubber (DPNR)-overlay agar medium forming a clearing zone. A transposon-insertion mutant, which had lost the ability to degrade DPNR, was isolated to identify the rubber degradation genes. Sequencing analysis indicated that the transposon was inserted into a putative oxygenase gene, latA . The deduced amino acid sequence of latA has 36% identity with that of roxA, which encodes a rubber oxygenase of Xanthomonas sp. strain 35Y. Phylogenetic analysis revealed that LatA constitutes a distinct group from RoxA. Heterologous expression in a Methylibium host and deletion analysis of latA indicated that the latA product is responsible for the depolymerization of DPNR. The quantitative reverse transcription-PCR analysis indicated that the transcription of latA is induced during the growth on DPNR. These results strongly suggest that latA is directly involved in the degradation of rubber in NS21. Graphical abstract: : LatA oxygenase is responsible for the cleavage of poly( cis -1, 4-isoprene) in Rhizobacter gummiphilus NS21.